Salt tolerance of corn genotypes (Zea mays L.) during germination and later growth - Radić Velimir; Beatović Damir; Mrđa Jelena (Journal of Agricultural Sciences (Belgrade), 2007)
Since corn is grown in climatically diverse regions and under different production conditions, assuming that high salinity in the substrate affect corn seed performance, such conditions were simulated in this study in order to examine their effects on seedling geminability and length in several corn genotypes. The study showed that the tested seeds tolerated the stress conditions up to a certain point. The studied genotypes differed in level of resistance to the stress conditions. Salt concentrations were determined, which were capable of affecting negatively seed germinability and seedling growth.